Delipidação química na produção in vitro e criopreservação de embriões bovinos - Diesel, Tiago Omar (2018)
Chemical delipidation has been used as an alternative to improve the cryotolerance of in vitro produced embryos (IVP). The aim of this study was evaluate the effect of L-carnitine (LC) on the development and survival of vitrified IVP bovine embryos by the Cryotop method in the first assay, and in the second trial the effect of LC and Forskolin on Cryotop cryopreserved embryos Experiment 1), or by modified slow freezing (Experiment 2), so mitochondrial activity, intracytoplasmic lipid (LI) content, cellular apoptosis (NCA) and hatching after heating were evaluated. In the first essay LC was used at the concentration of 0,6 mg/mL in maturation culture medium (IVM), embryo culture (IVC) and / or post-thawing (REC), in four treatments: without LC (Control), LC added to CIV (LCiv), LC to CIV + LC to REC (LCivR), and LC to MIV / CIV + LC to REC (LMivCR). The addition of LC increased the production of blastocysts in D7 by 28.6% (LCiv) and the amount of embryos grade I by 36.9% (LCivR), the re-expansion rate in 22,7% and hatching in 20.1% (LCiv), and mitochondrial activity was 1.9 times higher (P <0.001) (LCivR) than Control. The LI quantity was 29% lower in LCiv and LCivR and 50.2% in LMivCR compared Control (P <0.001). In the second experiment the embryos were cultured without addition of delipidators (Control), in the presence of 10μM of Forskolin added to the IVC in D5 (FORSK) or L-carnitine (0.6 mg / mL) added to the IVC and in post-thawing (LC). LC supplementation increased the production of blastocysts in D7 by 22.0% and grade I embryos by 30.1% (P <0.05), in relation to Control and FORSK. In Experiment 1, the re-expansion rate in LC increased (P <0.05) 28.9% in relation to FORSK. In Experiment 2, two Control treatments were used for slow freezing (Classic and Modified). Hatching after 48 hours was greater (P <0.05) in LC compared to FORSK and Classical and Modified Controls (77.5%, 41.9%, 40.5%, 40.8% respectively). In the LC treatment, there was a decrease (P <0.05) of 64.7% in the degenerate embryo rate in relation to the Classical Control. Treatment with delipidators reduced LI content (P <0.001) by 2.2 fold in FORSK and four times in the LC compared to Control. The addition of 0.6 mg / mL of L-carnitine to the culture medium and the post-thawing increased the rate of in vitro production of bovine embryos acting positively on mitochondrial potential, reducing the amount of intracellular lipids and cellular apoptosis and increasing cryotolerance of embryos submitted to the modified slow freezing protocol.